Thermoanalytical and Spectral Characterization of Cadmium(II) Complexes of Propantheline Bromide - Shanmukhappa, S.; Ramappa, P.G. (Asian Journal of Chemistry, 2010)
Synthesis, structure and properties of Cd(II) complexes of propantheline bromide (PPB) have been studied. The isolated complexes are characterised by various physico-chemical methods. Based on the data, tetrahedral structure has been suggested for the new metal complexes. Thermogravimetric studies of the complexes have been performed in order to establish the mode of their thermal stability. The thermal degradation process was found to proceed in two steps. Kinetic and thermodynamic parameters are evaluated on the basis of thermal degradation data. The values of activation energies are found to be in the range 8.5-33.5 kJ mol–1.